Follow-Up (Measurement) of Corrected QT Interval in Adult Patients before and after Lung Transplantation. (6th November 2017) - Bandorski, Dirk; Hoeltgen, Reinhard; Becker, Nicole; Padberg, Winfried; Bogossian, Harilaos; Wiedenroth, Christoph; Arlt, Matthias; Hamm, Christian; Seeger, Werner; Ghofrani, Hossein Ardeschir; Hecker, Matthias; Gall, Henning; et al.
Abstract : Background . Prolongation of the corrected QT (QTc) interval is well known for many drugs, some of which are an integral part of the therapeutic regimen after lung transplantation (LTX). Therefore, we investigated the QTc interval after LTX in the present study. Patients and Methods . The medical records of patients after LTX were studied for demographic data, indication of LTX, medication, and baseline and follow-up ECGs. The QT interval was corrected for the patient's heart rate using the different formulae of Bazett, Fridericia, Hodges, and Framingham. Results . Fifty-nine patients were included. The mean age ± SD was 55.6 ± 7.8 years (median 58 years). After LTX, QTc intervals showed no (relevant) changes during follow-up, even though all patients were treated with drugs (in combination) known to bear a risk of prolonged QTc interval and cortisone. The longest QTc intervals were obtained using Bazett's formula. Conclusion . The QTc interval did not increase under immunosuppressive medication after LTX in our cohort of patients. We speculate that the concurrent use of cortisone may shorten the QT(c) intervals or cancel out drug-induced prolongation of the QTc interval.